1993
DOI: 10.1262/jrd.39.269
|View full text |Cite
|
Sign up to set email alerts
|

Insemination Doses of Frozen-Thawed Semen in Seasonally Anestrous Ewes Treated with Two Different Progesterone-lmpregnated Intravaginal Devices.

Abstract: During the non-breeding season, a total of 176 Suffolk ewes at 3 sheep farms were treated with either a self-made, progesterone-impregnated intravaginal sponge (P sponge) or controlled internal drug release (CIDRR) for 9 days and an intramuscular injection of pregnant mare's serum gonadotropin (PMSG) 1 day before the cessation of progesterone treatment. At 44-52 h after treatment, 174 ewes were inseminated with 0.2, 0.1 or 0.05 ml of frozen-thawed ram semen per uterine horn with the aid of a laparoscope. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…The lambing rate was similar to our previous studies [2,7]. Although the fertility of inseminated ewes on the 3 farms were not directly c o m p a r a b l e d u e t o t h e d i f f e r e n c e i n t h e insemination doses between Farm T (0.2 or 0.4 ml) and the other two (S and M) farms (0.1-0.2 ml), the lambing rates on the 3 farms (48 to 64%) were not significantly different.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The lambing rate was similar to our previous studies [2,7]. Although the fertility of inseminated ewes on the 3 farms were not directly c o m p a r a b l e d u e t o t h e d i f f e r e n c e i n t h e insemination doses between Farm T (0.2 or 0.4 ml) and the other two (S and M) farms (0.1-0.2 ml), the lambing rates on the 3 farms (48 to 64%) were not significantly different.…”
Section: Discussionsupporting
confidence: 91%
“…A higher insemination dose (0.4 ml per head) had no advantage for pregnancy and lambing rates compared with a lower insemination dose (0.2 ml per head), which tended to show a high lambing rate (59.5 and 68.4%). For intrauterine insemination in ewes, a semen dose of 20 to 50 × 10 6 spermatozoa per ewe has provided satisfactory lambing rates (55-85%) [2][3][4]10]. But, it should be noted that the number of spermatozoa per insemination dose d o e s n o t i n d i c a te t h e n u m b e r o f m o ti l e spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those studies, we used fixed-time intrauterine AI with frozen-thawed semen containing egg yolk in ewes treated with different progestogens, including CIDRs, during the non-breeding and breeding seasons [15][16][17][18][19][20]. Conventional cervical insemination with frozen semen has not been fully accepted by the sheep industry due to low fertility (10-30%), although some studies in Norway have shown higher fertility (a lambing rate of over 70%) [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The CIDR was expelled from one of the 60 ewes during the insertion period, and the ewe was excluded from the present study. A fixedtime intrauterine insemination was performed for the remaining 59 ewes (30 and 29 ewes for the semen extender containing egg yolk and BSA, respectively) 43-47 h after removal of CIDR [15][16][17][18][19], regardless of the incidence of estrus. In regard to the insemination dosage (0.2 to 0.3 ml per ewe), the numbers of spermatozoa per ewe ranged from 5 0 t o 10 0 × 1 0 6 a nd t he n u m be r of m o ti l e spermatozoa per ewe was approximately half that (25 to 50 × 10 6 per ewe).…”
Section: Artificial Insemination (Ai)mentioning
confidence: 99%